Comparative study of three different fixation techniques for the treatment of Neer type IIb distal clavicle fractures: A retrospective cohort study - Liu, Zhi-Qing; Zhang, Ming-Shi; Zhou, Zi-Fei; Zhang, Lei; Zheng, Long-Po (Frontiers in Surgery, 2023)
Background Recently, a locking plate (LP) combined with a suture button was applied for distal clavicle Neer type IIb fractures. However, to our knowledge, there is limited information on clinical outcomes surrounding locking plates combined with a suture button in the treatment of Neer type IIb distal clavicle fractures. The aim of this study was to compare the outcomes among three different fixation techniques for the treatment of Neer type IIb distal clavicle fractures. Methods We performed a retrospective cohort study of 53 patients with Neer type IIb distal clavicle fractures who were treated with a hook plate (HP group, 16 patients), a locking plate alone (LP group, 18 patients), or a locking plate with a suture button (LPSB group, 19 patients) in our hospital between March 2014 and August 2019. The clinical and radiological outcomes were evaluated, including union time, postoperative complications, and function of the shoulder joint. Results The follow-up period was at least 2 years for all patients. All patients in the LPSB group achieved bone healing at the final follow-up. No significant differences were observed, including age, sex, side, time to surgery, duration of surgery, and mean follow-up period among the three groups (p > 0.05). The union time was shorter in the LPSB group than in the other two groups (p < 0.05). Postoperative complications were lower in the LPSB group than in the other two groups (p < 0.05). The visual analog scale score and Constant–Murley score in the LPSB group were better than those in the other groups at 3 and 6 months postoperatively (p < 0.05). Conclusion Compared with HP and LP alone, LPSB yields better clinical outcomes and lower complication rates in the treatment of Neer type IIb distal clavicle fractures.